Agricultural policy in the United States : evolution and economics - Novak, James L., Sanders, L.D, Hagerman, A.D; Sanders, Larry D.; Hagerman, Amy D. (New York Routledge, 2022)
"Agricultural Policy in the US: Evolution and Economics traces US agricultural policy from its colonial roots to the present, using economic concepts to analyze and interpret political and economic consequences. It also examines the processes by which agricultural policies are developed, and the government structure which supports the implementation of legislation passed by Congress. The book includes arguments for and against common tools of US agricultural policy, without influencing the reader in a particular direction. Each chapter contains review questions to support students' learning, and technical economic material is contained in optional appendices. The second edition examines the Agriculture Improvement Act of 2018 and sets the scene for future policy developments. Additionally, it looks at trade wars and the impact of black swan events like the COVID-19 pandemic on agricultural resilience. Agricultural Policy in the US is a valuable textbook for courses in agricultural economics and agricultural policy"--
Keywords: Agriculture and state--United states; Agriculture--Economics aspects--United States; Agricultural laws and legislation